EXPLORING AUDIOVISUAL DISSONANCE IN PRACTICE-BASED FILMMAKING: REPRESENTING DILEMMA IN BENDERA PUTIH - Utami, Citra Dewi; Arifianto, Budi Dwi (ARTISTIC : International Journal of Creation and Innovation, 2025)
Bendera Putih (2023), a short fiction film that strategically employs audiovisual dissonance to represent a profound dilemma, was produced in Yogyakarta as part of a community-based film initiative funded by the Yogyakarta City Cultural Service's Special Fund and was officially screened at the 2024 JAFF. Adopting a practice-based approach, this study investigates how the deliberate juxtaposition of visual and auditory elements crafts narrative ambiguity and intense emotional tension. Drawing on theories of cinematic dissonance, narrative disruption, and experiential learning, the article reflects on how asynchronous audio-visual pairings challenge audience expectations and provoke complex ethical and moral reflections. The socio-cultural context of the Yogyakarta community, known for upholding the value of "guyub rukun," critically informs the analysis of these creative decisions, illustrating how the local context shapes both the storytelling approach and the film's reception. The findings contribute to the discourse on alternative narratives in Southeast Asian independent cinema, underscoring the capacity of practice-based research to illuminate the affective and ethical dimensions of filmmaking.